2015
DOI: 10.1038/ncb3117
|View full text |Cite
|
Sign up to set email alerts
|

EGF-mediated induction of Mcl-1 at the switch to lactation is essential for alveolar cell survival

Abstract: Expansion and remodelling of the mammary epithelium requires a tight balance between cellular proliferation, differentiation and death. To explore cell survival versus cell death decisions in this organ, we deleted the pro-survival gene Mcl-1 in the mammary epithelium. Mcl-1 was found to be essential at multiple developmental stages including morphogenesis in puberty and alveologenesis in pregnancy. Moreover, Mcl-1-deficient basal cells were virtually devoid of repopulating activity, suggesting that this gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 60 publications
4
77
0
Order By: Relevance
“…(c) Distinct mammary epithelial cell populations may express differing levels of miRs, and aggressive PDAs may originate from cells with intrinsically low miR-143/145 expression. Indeed, data mining of miR expression from Fu et al (64) suggests that miR-145 may be differentially expressed in basal versus luminal mouse mammary cell lineages. However, in preliminary analyses with mouse pten-deficient mammary epithelial cells, we observed no significant difference in miR-143 or miR-145 expression in FACS-purified basal, luminal, luminal progenitor, or mature luminal mammary epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…(c) Distinct mammary epithelial cell populations may express differing levels of miRs, and aggressive PDAs may originate from cells with intrinsically low miR-143/145 expression. Indeed, data mining of miR expression from Fu et al (64) suggests that miR-145 may be differentially expressed in basal versus luminal mouse mammary cell lineages. However, in preliminary analyses with mouse pten-deficient mammary epithelial cells, we observed no significant difference in miR-143 or miR-145 expression in FACS-purified basal, luminal, luminal progenitor, or mature luminal mammary epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that filamentous actin in the form of long, thick, contractile stress fibers may be an artifact of in vitro culture stimulated by the attachment of cells to rigid substrates, such as plastic or glass. However, there are a few examples of cells with prominent stress fibers in vivo, including cells involved in the closure of epithelial sheets during embryogenesis, myoepithelial cells in wounds (1,2) and in mammary glands (3), and endothelial cells of large blood vessels (4)(5)(6). A common feature is the high level of mechanical stress experienced by cells with stress fibers.…”
Section: Introductionmentioning
confidence: 99%
“…MMTV-Cre (A strain) mediates a high frequency of excision (>95%) in both basal and luminal cells 22,33 . Mammary tumors that arise in this model express abundant amounts of RANK and a lower amount of RANKL, whereas most tumors from Trp53 +/− mice did not (Fig.…”
mentioning
confidence: 99%